Iron-deficiency and pruritus: a possible explanation of their relationship - Tammaro, Antonella; Chello, Camilla; di Fraia, Marco; Giordano, Domenico; Magri, Francesca; Zollo, Verdiana; Parisella, Francesca Romana; De Marco, Gabriella (International Journal of Research in Dermatology, 2018)
Pruritus of unknown origin is defined as itching lasting for more than 3 weeks without a clear identifiable cause. Aetiology of itching is wide ranging and includes chronic renal failure, cholestasis and internal malignancy. Iron deficiency has been described to be causative of pruritus but the mechanism underlying this association remains unclear. We report the case of a female patient with iron deficiency anemia and generalized pruritus, resolved after intravenous administration of iron-complex supplements and we explained a possible mechanism between this association.